Comparison of the lenght-weight relationship between starved and fed Scylla tranquebarica crablets. - Arroyo, Ritchel B.
This study aimed to determine the length-weight as well as the width-weight relationships of the Scylla tranquebarica crablets when starved and fed during the intermolt and premolt stages. Molt stages were identified and then the crablets were subjected to feeding or starvation for 36 days., Regression anlysisshowed the length-weight relationship of Scylla tranquebarica crablets, including carapace length, carapace width and body weight when fed and starved. Regression lines for each category differed from one another. Results showed that the fed crablets in intermolt and premolt stages greater body weight gain per unit carapace length and carapacewidth. The intermolt fed gave the highest weight gain per unit length and unit width among the treatments. Equations for interconversions of length and weight and for length and width are reported for the premolt and intermolt stages when fed and starved.